Form And Structure Selected Songs From Kidung Penghiburan Consolation Worship In GKI Indramayu - Dm, Alberta; Muttaqin, Moh. (Jurnal Seni Musik, 2020)
Analysis of music form aims to peel and unravel the song thoroughly so that the contained elements in it can be found. The problem statement in this research is analysis of form song from Kidung Penghiburan. This research uses descriptive qualitative method and using several data collection techniques, including observation and documentation studies. Data will be validated by data triangulation. Data analysis techniques in this research uses data reduction, data presentation, conclusion withdrawal and verification. The result of this research showed that the songs from Kidung Penghiburan titled Pintu Gebang Terbukalah, Jalan Hidup Tak Selalu, Makin Dekat Tuhan, and Tuhan Allah Beserta Engkau are the two-part songs with different phrases arrangement and motif tabulation. Pintu Gebang Terbukalah’s form is A (a a’), B (b y), Jalan Hidup Tak Selalu’s form is A (a a’), A’ (a x), B (b y), Makin Dekat Tuhan’s form is A (a a’), B (b a’), and Tuhan Allah Beserta Engkau’s form is A (a a’), B (b b’).